2009
DOI: 10.1002/lary.20254
|View full text |Cite
|
Sign up to set email alerts
|

Gene single nucleotide polymorphism accumulation improves survival in advanced head and neck cancer patients treated with weekly paclitaxel

Abstract: Response rate and OS were significantly higher in patients with two or more accumulated SNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Study populations of previous publications were mostly hospital-based and ranged from 47 to 531 HNC cases [10, 13]. Further, the present study population included 922 White cases and 305 African Americans cases which allowed for estimation of race-specific HRs.…”
Section: Discussionmentioning
confidence: 99%
“…Study populations of previous publications were mostly hospital-based and ranged from 47 to 531 HNC cases [10, 13]. Further, the present study population included 922 White cases and 305 African Americans cases which allowed for estimation of race-specific HRs.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search yielded 58 publications. The following studies were excluded: two were published in Chinese(Yang et al, 2008b, Wen et al, 2007) and one in Polish(Rusin et al, 2008); three did not report gene polymorphisms(Cheng et al, 2002, Wei et al, 2005, Yang et al, 2006); two assessed the association between gene polymorphisms and survival(Grau et al, 2009, Handra-Luca et al, 2007); seven evaluated treatment efficacy(Bozec et al, 2007, Carles et al, 2006, Fountzilas et al, 2009, Jun et al, 2008, Kornguth et al, 2005, Quintela-Fandino et al, 2006, Werbrouck et al, 2009); one assessed the potential of gene polymorphisms as predictive and prognostic markers(Koh et al, 2009); two studies were conducted in patients only(Geisler et al, 2005, Hsieh et al, 2003); one study evaluated the potential of gene polymorphisms as risk modifiers of the association of oral contraceptives and oral cancer risk(Applebaum et al, 2009); one did not evaluate the genes of interest(Gajecka et al, 2005a); three studies evaluated the risk of oral leukoplakia(Majumder et al, 2009, Wang et al, 2007, Yang et al, 2008a); two studies evaluated the risk of secondary primary neoplasms(Gal et al, 2005); two reported on haplotypes only(Michiels et al, 2007, Majumder et al, 2009) and one included lung cancer under upper-aerodigestive tract (UADT) cancer(Buch et al, 2005). Therefore, 30 studies that included 19,343 individuals (7,291 cases and 12,052 controls) were considered for the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…observed a poorer response in these patients [54]. The association with efficacy of paclitaxel treatment is somewhat less clear; ABCB1 variant alleles have been associated with shorter progression-free survival, overall survival and lower disease control rates in Koreans [51,55], but greater response rate [56,57] and progression-free survival [58] in other populations.…”
Section: Pharmacogeneticsmentioning
confidence: 99%